Cuprizone-induced Demyelination in Mouse Brain is not due to Depletion of Copper. (September 2022) - Morgan, Megan L.; Teo, Wulin; Hernandez, Yda; Brideau, Craig; Cummins, Karen; Kuipers, Hedwich F.; Stys, Peter K.
The cuprizone (CPZ) model allows the study of the biochemical processes underlying nonautoimmune-mediated demyelination, remyelination, and chronic white matter disease progression. CPZ is a copper (Cu) chelator that chiefly causes oligodendrocyte apoptosis in the corpus callosum and cerebellum when administered in the mouse diet. While disruption of Cu homeostasis is known to cause neurodegeneration (as is observed in Wilson's and Menkes disease), no consensus exists to date as to CPZ's mechanism of action. We sought to determine whether CPZ-induced pathology is due to Cu depletion as is generally believed. Cu supplementation in chow, in stoichiometric excess to the added CPZ, did not reduce CPZ-induced demyelination in C57Bl/6 mice. Moreover, equivalent doses of other known Cu chelators neocuproine and D-penicillamine (D-Pen) failed to induce central nervous system (CNS) demyelination. Since administration of D-Pen in the treatment of Wilson's disease can induce hypocupremia, we next sought to recreate penicillamine-induced Cu deficiency to compare with purported CPZ-induced Cu deficiency. The resulting clinical phenotype and histopathology were unlike that of CPZ. D-Pen-treated mice exhibited digit paralysis, tail flaccidity, subcutaneous hemorrhaging, and optic and sciatic neuropathy, all of which were prevented with Cu supplementation. No demyelination of the corpus callosum or cerebellum was observed, even with D-Pen doses tenfold higher than CPZ. Intriguingly, addition of D-Pen to the CPZ diet paradoxically prevented demyelination in a dose-dependent manner. Summary Statement: The demyelinating effects of CPZ are not due to Cu deficiency but are instead consistent with acute toxicity of a CPZ + Cu complex.